Airflow limitation in croup - Jaroslawski, ML (Division of Biomedical Engineering, 2017)
This thesis investigates a mechanism for air flow limitation in children with croup. Croup is a common condition affecting many young children. Infection (usually viral) causes swelling of the mucosa in the subglottic region of the airway with consequent narrowing of the airway. Although researchers have investigated croup for the past sixty years, there is still very little information available on how croup affects air flow dynamics. The current theory assumes that the stenosis formed by croup in the subglottis of infants leads to a dynamic collapse of the extrathoracic trachea (Chernick, 1990). According to this literature, the dynamic collapse of the extrathoracic trachea will limit the inspiratory flow. It was believed that in severe cases of croup, the dynamic collapse may even temporarily block the airways. In order to investigate the mechanism for air flow limitation in croup the author used the intrathoracic pressure - flow traces from twenty patients with croup, four patients who had been intubated for croup and five normal subjects. Laryngeal X-rays from another twenty patients with croup were analysed as well as five videos, made during laryngoscopy, of the subglottic cross-sectional area of an additional five patients with croup requiring intubation. All data used in this project was collected by an experienced paediatrician from the Red Cross War Memorial Children's Hospital who is also the supervisor of this thesis. Both the video and the X-ray data showed that the dynamic collapse of the trachea contributes much less to airflow obstruction than the subglottic swelling itself. The hypothesis investigated in this thesis is that air flow becomes restricted due to wave speed limitation. According to the theory of wave speed limitation, an increase in driving pressure (the intrathoracic pressure) does not increase the flow if the speed of the air particles exceeds the wave speed. In our case the wave speed is the speed of sound within the lumen of the compliant, narrowed airway. In order to test that theory, it was necessary to obtain the flow, the driving pressure in the subglottis and the cross-sectional area of the subglottis of patients with croup. Unfortunately, the measurement of subglottal cross-sectional areas from videos made during laryngoscopies, proved to be impossible due to both ethical and practical constraints. The measurement of the subglottal cross-sectional areas from X-rays was also difficult in practice. Therefore, the cross-sectional area is calculated. The general orifice equation is modified m order to calculate the subglottal cross-sectional areas in patients with croup. Two methods are used to test the hypothesis of wave speed limitation: i) The wave speed limitation formula. The wave speed limitation formula directly calculates the maximum flow from the pressure - flow data. Hereafter the calculated maximum flow is compared with the measured flow. ii) A lumped component model. A nonlinear, lumped component model has been used to calculate the flow from the driving pressure (intrathoracic pressure). Flow is not limited in this model and an increase in driving pressure will result in a corresponding increase in flow. The flow which is calculated using this model has also been compared to the measured flow. It was found that, in children with croup, there is a good correlation (r=0.82) between calculated and measured values of maximum flow using the wave speed limitation model. The slope of the linear fit using a least square's approximation is 0.98 and this linear relationship is valid for a 0.05 level of significance for Conover's nonparametric test (Daniel and Terrell, 1989). The lumped component model was able to fit the inspiratory flow data with a small sum of square error in the case of both normal ((7.56 ± 0.86) · 10⁻⁹ (ml/s)²) and intubated patients ((3.2 ± 0.75)·10⁻⁹ (ml/s)²). However, the error rose dramatically in patients with croup ((2.04 ± 0.5) -10⁻⁸ (ml/s)²) thus indicating that the lumped component model is no longer valid in these patients. It is concluded that the measured flow velocities in patients with croup approach the calculated velocity of sound in the region of the subglottic swelling, and that the wave speed theory accurately describes the flow limitation. Further support of this is the fact that the lumped component model, which does not incorporate a flow limiting mechanism, breaks down in patients with croup.